Error-prone Translesion Synthesis Past DNA-Peptide Cross-links Conjugated to the Major Groove of DNA via C5 of Thymidine - Wickramaratne, Susith; Boldry, Emily J.; Buehler, Charles; Wang, Yen-Chih; Distefano, Mark D.; Tretyakova, Natalia Y. (The Journal of biological chemistry, 2015)
DNA-protein cross-links (DPCs) are exceptionally bulky, structurally diverse DNA adducts formed in cells upon exposure to endogenous and exogenous bis-electrophiles, reactive oxygen species, and ionizing radiation. If not repaired, DPCs can induce toxicity and mutations. It has been proposed that the protein component of a DPC is proteolytically degraded, giving rise to smaller DNA-peptide conjugates, which can be subject to nucleotide excision repair and replication bypass. In this study, polymerase bypass of model DNA-peptide conjugates structurally analogous to the lesions induced by reactive oxygen species and DNA methyltransferase inhibitors was examined. DNA oligomers containing site-specific DNA-peptide conjugates were generated by copper-catalyzed [3 + 2] Huisgen cyclo-addition between an alkyne-functionalized C5-thymidine in DNA and an azide-containing 10-mer peptide. The resulting DNA-peptide conjugates were subjected to steady-state kinetic experiments in the presence of recombinant human lesion bypass polymerases κ and η, followed by PAGE-based assays to determine the catalytic efficiency and the misinsertion frequency opposite the lesion. We found that human polymerase κ and η can incorporate A, G, C, or T opposite the C5-dT-conjugated DNA-peptide conjugates, whereas human polymerase η preferentially inserts G opposite the lesion. Furthermore, HPLC-ESI−-MS/MS sequencing of the extension products has revealed that post-lesion synthesis was highly error-prone, resulting in mutations opposite the adducted site or at the +1 position from the adduct and multiple deletions. Collectively, our results indicate that replication bypass of peptides conjugated to the C5 position of thymine by human translesion synthesis polymerases leads to large numbers of base substitution and frameshift mutations.DNA-protein conjugates can be induced by reactive oxygen species and proteolytically cleaved to the corresponding peptide conjugates. Polymerase bypass past C5-dT peptide conjugates catalyzed by human polymerases η and κ gives rise to base substitutions and deletions. Replication past C5-T peptide conjugates is mutagenic. This study provides the first evidence for error-prone replication of DPCs cross-linked to pyrimidines in DNA.